Institutions for effective business-government collaboration: Micro mechanisms and macro politics in Latin America - Ben Ross Schneider (Inter-American Development Bank (IDB), 2013)
What makes for effective cooperation between government and business in industrial policy? Core research questions on the institutional design of arrangements for business-government interactions focus on three main functions: i) maximizing the benefits of dialogue and information exchange; ii) motivating participation through authoritative allocation; and iii) minimizing unproductive rent seeking. Countries with more experiences of public-private collaboration (PPC) tend to have more pragmatic governments and better organized and informally networked private sectors. Effective cooperation also depends on the macro context, in particular the nature of the political system and the alternative avenues it provides for business politicking, especially through parties, networks and appointments, the media, and campaign finance. Lastly, the structure and strategies of big domestic businesses-mostly diversified, family-owned business groups-affects their preferences and interest in collaborating in industrial policy.
hdl:11319/4674
Keywords: D72; L52; 330; Industrial policy; Public-private collaboration; Rent-seeking